The Role of Education and the Mahalla Institute in Forming the Personality of the Person - Muzaffarov Umidjon Ismoil ogli; Kandov Bahodir Mirzayevich (Central Asian Journal of Theoretical and Applied Science, 2022)
This article reveals that one of the urgent tasks today is the fight against globalization, especially its influence on changing national customs, traditions, values and mores, to form a factor that can serve as a shield and apply it to our society. At the same time, the article analyzes the growing threats and dangers to our national identity and spiritual values under the influence of globalization and information attacks, various destructive ideas.